2018
DOI: 10.1017/iop.2018.84
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Evaluation of the State of Assessment and Development for Senior Leaders

Abstract: Practice and research with senior leaders can be rewarding but also challenging and risky for industrial and organizational (I-O) psychologists; the fact that much of the work with these populations is difficult to access elevates these concerns. In this article we summarize work presented by prominent researchers and practitioners at a symposium organized to share common practices and challenges associated with work at higher levels of organizational management. We review implications for research and practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…Our systems thinking of corporate university provides one answer to the critical question asked by Reynolds et al (2018), "How to address questions of readiness for specific future roles within the context that will exist for the role and acknowledge that context is constantly shifting?" (p. 638).…”
Section: Defining a Corporate University's Role For Sustainable Organmentioning
confidence: 99%
See 3 more Smart Citations
“…Our systems thinking of corporate university provides one answer to the critical question asked by Reynolds et al (2018), "How to address questions of readiness for specific future roles within the context that will exist for the role and acknowledge that context is constantly shifting?" (p. 638).…”
Section: Defining a Corporate University's Role For Sustainable Organmentioning
confidence: 99%
“…Proposition 2: A corporate university that functions as a learning mechanism to integrate processes of strategy making, communicating, implementing, and revising will strengthen its organization's sustainable competitive advantage. Reynolds et al (2018) identified clear communication and alignment across the organization as accepted wisdom for assessing senior leaders. A corporate university under our definition provides a mechanism for effective alignment not only for leader assessment but also for strategic management as a whole.…”
Section: Defining a Corporate University's Role For Sustainable Organmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors begin the article by advocating the use of validated tools to inform ongoing leader development, much as we, as a field, advocate the use of validated tools in other domains, such as selection or performance appraisal (Reynolds et al, 2018). In discussing assessment, the authors note that its successful implementation is contingent on the broader context in which the leader's development is taking place.…”
mentioning
confidence: 99%